Analisis Prinsip Moral dalam Nussa dan Rara, sebuah Film Animasi “Spesial Ramadhan ” : (Framing Model Gamson dan Modigliani Analisis) - Melisa Melisa; Zahra Zahra; Zainul Irfan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Abstract: Film is one of the most widely used mass media because it combines visual and rhythmic elements into one complete unit. Film also functions as a propaganda and educational tool to spread moral and cultural values ​​to the community. Nussa and Rara is an animated film that contains moral lessons and educational values. Therefore, this study aims to analyze the moral principles contained in the Nussa Dan Rara film in the episode